Problematics of Student Activism in the Subject of Akidah Akhlak - Ikbal Lupariq; Triwid Syafarotun Najah; Istiyati Mahmudah (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze student engagement in Aqidah Akhlak learning at MTs Darul Ulum Palangka Raya. Student engagement in the learning process significantly impacts their understanding and application of the religious values taught. The research method used is descriptive qualitative, with observation, interviews, and documentation as data collection techniques. The results show that, although there is good interaction between students and teachers, most students tend to be passive, especially when the lecture method is more dominant. Several factors influencing student engagement include low interest, peer distractions, and monotonous teaching methods. It is recommended that teachers develop more varied and engaging teaching strategies to encourage greater student participation in learning.